Evaluating the effectiveness of e-learning for soft skills training - PESSO, Manon (2015)
Thanks to the development of Internet technologies, e-learning platforms became a widespread tool to provide training on both hard and soft skills in a cost-effective way. However, the debate is still ongoing about the efficiency of soft skill e-learning. The goal of this dissertation is thus to evaluate the efficiency of e-learning for soft skills training by studying the case of a French regional bank’s e-learning system. To do this, I analysed the literature on learning, e-learning and training evaluation and decided to base the study on the Kirkpatrick model (1996). Nine in-depth, semi-structured interviews were carried out to give a detailed insight of employees’ experience of the platform. The data revealed that the perceived usefulness of the system among employees was quite low. Then, they suggested that the platform was useful for reviewing already approached topics and building on existing skills but not for learning new competences from scratch. However, soft skill e-learning seems to have created changes in users’ behaviour even if they are sometimes subtle. Finally, the cost-effectiveness of the platform seems to be threaten by the low level of users’ connexions. Thus the data enabled to highlight main factors explaining employees’ reluctance: the impossibility to isolate from the daily activity, the lack of guidance on the platform and the lack of time.